An emotional state : the politics of emotion in postwar West German culture - Parkinson, Anna M. (Social history, popular culture, and politics in Germany, 2017)
"This literary-historical study seeks to dismantle the prevailing notion that Germany, in the period following the Second World War, exhibited an 'inability to mourn,' arguing that in fact the period experienced a surge of affect. Anna Parkinson examines the emotions explicitly manifested or addressed in a variety of German cultural artifacts, while also identifying previously unacknowledged (and under-theorized) affective structures implicitly at work during the country's national crisis. Much of the scholarship in the expanding field of affect theory distrusts Freudian psychoanalysis, which does not differentiate between emotion and affect. One of the book's major contributions is that it offers an analytical distinction between emotion and affect, finding a compelling way to talk about affect and emotion that is informed by affect theory but that integrates psychoanalysis. The study draws on the psychoanalytic writings of Freud, Margarete and Alexander Mitscherlich, and André Green, while engaging with interdisciplinary theorists of affect including Barbara Rosenwein, Lauren Berlant, Ann Cvetkovich, and Eve Kosofsk Sedgwick, among many others; 'Offers a truly original, even pathbreaking, contribution to the study of postwar West German culture, while making a very important intervention in the theoretical debate on the study of emotions. Its potential audience includes not only historians and literary critics but the rapidly growing, strongly interdisciplinary community of emotion scholars'...Frank Biess, University of California, San Diego; 'Beautifully written, the book conveys its insights in clear prose and through carefully argued, illuminating readings. Parkinson thoughtfully frames each of her chapters as an inquiry, not simply into the textual nuances of argumentation and rhetoric, but into these texts' place in larger, pragmatic contexts that Parkinson calls 'scenarios.' Consequently, Parkinson attends n